Matematyka
95mariola59
31

zad 1 . a) 3x-5=4+2x b)-5x+10=-2x-8 c)-5x-17=-9x+3 d)7x+14=5x-22 e)2x-4+5x=x+2 f)-3+2x-6=3-4x g)7x+2=5+3x+9 h)-5x+12+x=2x-12 zad 2 . a)2(x-3)+3(4-x)=5 b)3(x-4)-2(2x-5)=-4 c)2(x+4)-5(x+3)=2 d)-2(x+3)+4(2x+3)=-6 zad 3 . a) (4-2x)-(x+3)=(x-5)+(-3-x) b)(3-2x)+(3x+4)=-(3-2x)+(5x+4) c)-(x+3)+(2x-1)=(1+4x)+(3+x) d)-(x+3)-(2x+8)=(-3-2x)+(2x+1) zad 4 . a)(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

+3
(2) Odpowiedź
Namalowana95

Zad1   a) 3x-5=4+2x x=9   b)-5x+10=-2x-8 -3x=-18 x=6   c)-5x-17=-9x+3 4x=20 x=5   d)7x+14=5x-22 2x=-36 x=-18   e)2x-4+5x=x+2 7x-4=x+2 6x=6 x=1   f)-3+2x-6=3-4x -9+2x=3-4x 6x=12 x=2   g)7x+2=5+3x+9 7x+2=14+3x 4x=12 x=3   h)-5x+12+x=2x-12 -4x+12=2x-12 -6x=-24 x=4   zad 2 .  a)2(x-3)+3(4-x)=5 2x-6+12-3x=5 -x+6=5 -x=5-6 x=1   b)3(x-4)-2(2x-5)=-4 3x-12-4x+10=-4 -x-2=-4 -x=-2 x=2   c)2(x+4)-5(x+3)=2 2x+8-5x-15=2 -3x-7=2 -3x=9 x=-3   d)-2(x+3)+4(2x+3)=-6 -2x-6+8x+12=-6 6x+6=-6 6x=-12 x=-2   zad 3 .  a) (4-2x)-(x+3)=(x-5)+(-3-x) 4-2x-x-3=x+5-3-x 1-3x=2 -3x=1 x=-1/3   b)(3-2x)+(3x+4)=-(3-2x)+(5x+4) 3-2x+3x+4=-3+2x+5x+4 7+x=1+7x 6=6x x=1   c)-(x+3)+(2x-1)=(1+4x)+(3+x) -x-3+2x-1=1+4x+3+x x-4=5x+4 -4x=8 x=-2   d)-(x+3)-(2x+8)=(-3-2x)+(2x+1) -x-3-2x-8=-3-2x+2x+1 -3x-11=-2 -3x=9 x=-3   zad 4 .  a)(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 3-2x-x-4-2x-5=3x-4-5x-7 -6-5x=-2x-11 -3x=-5 x=5/3   b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 4-x-2x-3+x-4=-2x+3-x-7 -3-2x=-3x-4 1=-x x=-1   c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 4x-5+x-7-2x+8=-3x+4-x+6 3x-4=-4x+10 7x=14 x=2   d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) -4+2x-2x-4=3x-1+2x-5-7+3x -8=8x-13 5=8x x=5/8    

bejbuśka

Zad.1 a)3x-5=4=2x 3x-2x=4+5 x=9 b)-5x+10=-2x-8 -5x+2x=-8-10 -3x=-12/(-3) x=4 c)-5x-17=-9x+3 -5x+9x=3+17 4x=20/4 x=5 d)7x+14=5x-22 7x-5x=-22-14 2x=-36/(-2) x=-18 e)2x-4+5x=x+2 2x-x=2+4 x=6 f)-3+2x-6=3-4x 2x+4x=3+6+3 6x=12/6 x=2 g)7x+2=5+3x+9 7x-3x=9+5-2 4x=12/4 x=3 h)-5x+12+x=2x-12 -5x+x-2x=-12+12 -6x=0 Zad.2 a)2(x-3)+3(4-x)=5 2x-6+12-3x=5 -x=5+6-12 -x=-1/(-1) x=1 b)3(x-4)-2(2x-5)=-4 3x-12-4x+10=4 -x=-2/(-1) x=2 c)2(x+4)-5(x+3)=2 2x+8-5x-15=2 -3x=2+15-8 -3x=9/(-3) x=-3 d)-2(x+3)+4(2x+3)=-6 -2x-6+8x+12=-6 6x=-6+6-12 6x=-12/6 x=-2 Zad.3 a) (4-2x)-(x+3)=(x-5)+(-3-x) 4-2x-x-3=x-5-3-x -2x-x-x+x=-3-5+4 -3x=-4/(-3) x=4/3 b)(3-2x)+(3x+4)=-(3-2x)+(5x+4) 3-2x+3x+4=-3+2x+5x+4 -2x=-2/(-2) x=1 c)-(x+3)+(2x-1)=(1+4x)+(3+x) -x-3+2x-1=1+4x+3+x -4x=8/(-4) x=-2 d)-(x+3)-(2x+8)=(-3-2x)+(2x+1) -x+3-2x-8=-3-2x+2x+1 -3x=3/(-3) x=-1

Dodaj swoją odpowiedź